Development of A Handcycle for The Disabled Based on Alternative Materials and Sustainable Electricity Using The Vdi 2221 Method To Improve Ergonomics and Energy Efficiency - Arifiansah, Arifiansah; Anwar, Syahrul; Maryadi, Maryadi; Sari, Mulyani Indah; Fauziah, Dita Anggun; Asyroflie, Farrel; Wijaya, Adje (Dinasti International Journal of Education Management and Social Science, 2025)
Handcycle is a transportation device in the form of a tricycle controlled by the rider’s arms through a chain and crank transmission. This research aims to design and develop a handcycle prototype for people with disabilities by applying the VDI 2221 systematic design method. The innovation focuses on using 6061 aluminum as the main frame, reducing weight by 46.6% compared to ST 37, and an ergonomic seat designed based on anthropometric data. To support mobility, the system integrates a 36 Volt/350 Watt a BLDC motor powered by a 36-volt, 10-Ah lithium-ion battery. This configuration theoretically enables a range of ±25–30 km per charge with a maximum speed of 45 km/h. A 300 WP solar panel is also employed as a renewable energy source, enhancing sustainability. The product development follows four main VDI 2221 stages: needs analysis, concept design, design development with CAD details, prototyping, and testing. The result is a handcycle prototype that combines ergonomics, efficiency, and eco-friendliness, offering a practical mobility solution for people with disabilities while promoting renewable energy utilization. This study demonstrates how lightweight materials and sustainable electrical systems can significantly improve assistive transportation technology.